Effectiveness of Use of Early Childhood Education Operational Assistance Funds in Improving Education for Early Children in Sesayap District, Tana Tidung Regency - Arta, Lusiana Dewi; Muhtar, Entang Adhy; Sudirah, Sudirah (Journal of Social Research, 2023)
This research aims to analyze the effectiveness of the early childhood education operational assistance fund in improving early childhood education in Tana Tidung Regency. This research employs a qualitative research method, which is a method used to study natural conditions where the researcher acts as the key instrument. The data generated is descriptive in nature, and data analysis is conducted inductively. The data obtained in this study utilize data collection techniques such as in-depth interviews, observations, and documentation. The effectiveness of the early childhood education operational assistance fund implemented by the Department of Education and Culture in Tana Tidung Regency analyzed through three factors (Goal Attainment, Integration, and Adaptation), is generally underway, but not fully effective. This can be evidenced in terms of goal achievement, where fund distribution is on target and timely, and in terms of procedures and benefits, where it effectively alleviates the burden of education expenses. Concerning the factor of integration, which involves processes of socialization, clarity of information, synchronization of activities, transparency, and accountability in the utilization of the School Operational Assistance fund, there are still weaknesses in terms of synchronization between schools and the department regarding the importance of openness and transparency in school financial management. Regarding the adaptability factor, analyzed through the ability to respond to changes, the availability of infrastructure and the utilization of technology in the School Operational Assistance fund is not yet fully effective. This can be observed in terms of human resources' proficiency in information technology and the inadequacy of infrastructure.